ANALISIS PENGARUH RASIO-RASIO KEUANGAN TERHADAP DIVIDEND PAYOUT RATIO (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2013) - Novaliana Rahmi; Taufeni Taufik; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research was to find out and analyze the effect of return on investment, current ratio, debt to equity ratio and asset growth on dividend payout ratio on the manufacturing companies listed in Indonesia Stock Exchange. The population used in this research is 141 manufacturing companies, and the sample that used is 37 manufacturing companies, analysis of data using multiple regression. Based on the result of the data analysis where t table of -1.982, value of t for return on investment amounted to 4.473 (p value 0.000), current ratio of -1.448 (p value 0.151), debt to equity ratio of -0.715 (p value 0.476) and asset growth amounted to -4.301 (p value 0.000). If the p value is less than alpha (significance) then Ha is accepted, whereas if the p value is greater than alpha (significance) then Ha is rejected. So it can be concluded that the Return on Investment (ROI) significantly affects the dividend payout ratio, current ratio does not significantly influence the dividend payout ratio, Debt to Equity Ratio (DER) did not significantly influence the dividend payout ratio, and growth  asset significant effect on dividend payout ratio. With a total value of R square 0.271, which means that only 27.1% of independent variables had an influence on the dependent variable. While the remaining 72.9% is influenced by other variables not included in the regression model.Keywords: Dividend Payout Ratio, Return on Investment, Current Ratio, Debt to Equity Ratio, and Asset Growth.